Editorial: Scientific and technological revolution - El Director (2011)
If we intend to take a big look at the Peruvian University, UNI and scientific and technological research, we must try to join some points that fate and opportunity have placed at our disposal to try to reflect on them, with the purpose of initiating a deep reflection on what should be the new path of the IECOS Journal in the new stage of its existence that begins and our participation in the organs of the Faculty and UNI.